Elastic Plate Osteosynthesis of Long Bone Fractures usingVeterinary Cuttable Plates in Young Dogs - D, Sai Bhavani D; NVV, Hari Krishna; M, Sreenu; G Venkat Naidu, (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Twelve dogs below one year of age presented with a history of forelimb or hindlimb lameness, suggestive of either radius or tibia  fracture were selected to study the fracture stabilisation by Elastic Plate Osteosynthesis (EPO) technique using 2.0/2.7 mm Veterinary  Cuttable Plate (VCP). The implants were selected according to body weight and bone size. Post-operatively, the dogs were evaluated  by clinical, radiographical and lameness grading. Primary healing was observed in eight cases and secondary healing in four cases.  Fracture healing was observed by 30th post-operative day in most of the cases. The dogs regained full limb functionality by 15-30 days  post-surgery. All the animals regained normal return to weight bearing early (within one month) with excellent to good limb usage. Plate  removal was done in all cases on 5-8 weeks post-surgery. No major post-operative complications were observed. To conclude, the VCP  used was inexpensive and the EPO technique using VCP was useful for long bone fractures of young dogs making it suitable for use in  Veterinary practice and the technique resulted in early weight bearing and good functional limb out come without any complications
Keywords: young dogs; Radial and Tibial diaphyseal fractures; Veterinary Cuttable Plates; Elastic Plate Osteosynthesis